Antimicrobial resistance in intensive care patients hospitalized with SEPSIS: a comparison between the COVID-19 pandemic and pre-pandemic era - Falasca, Katia; Vetrugno, Luigi; Borrelli, Paola; Di Nicola, Marta; Ucciferri, Claudio; Gambi, Alessandra; Bazydlo, Magdalena; Taraschi, Giorgia; Vecchiet, Jacopo; Maggiore, Salvatore Maurizio (Frontiers in Medicine, 2024)
Introduction: Coronavirus disease 2019 (COVID-19) is a highly contagious viral illness caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). It has had a dramatic effect on the world, resulting in millions of deaths worldwide and causing drastic changes in daily life. A study reported that septic complications were associated with high mortality in COVID-19 patients. The aim of this study wereThis study aimed to evaluate how the COVID-19 pandemic changed the pre-pandemic and post-pandemic prevalence of sepsis in ICUs and to to evaluate the different risk factors associated with mortality and the different diffusion of microorganisms and their resistance. Materials and Methods: We carried out a single center centre retrospective observational clinical study that observed observed all the patients in in the ICU of the SS Annunziata Hospital in Chieti (Italy) who had a diagnosis of sepsis and presented a bacterial isolate from blood culture. The diagnosis of sepsis was made in accordance withby SEPSIIS III criteria. We enrolled all in-patients in the ICU from January 2018 to December 2021. We divided the patients into three groups: (1) Np (Non Pandemic period) hospitalized in 2018-2019, (2) Pp (Pandemic Period)-COVID hospitalized in 2020-2021 with a diagnosis of COVID-19, and (3) Pp noCOVID patients hospitalized 2020-2021 without a diagnosis of COVID-19.